Treatment of animal farm wastewater using Ipomoea Aquatica and Llmnocharis Flava - Ling, Teck Yee; M. J., Diana (Proceedings 4th International Conference on Natural Resources & Environmental Management and Environmental Safety & Health, 24-26 Nov. 2009, Kuching, 2009)
Wastewater from intensive animal farming is rich in organic matter and nutrients. Wetland treatment technology is economical and suitable for application in the tropics. Plants that occur naturally in the tropical wetland system can play an important role in the treatment of wastewater. Therefore, in this study two aquatic plants (Ipomoea aquatica and Limnocharis flava) were investigated for their efficiency in the uptake of nutrients from pig farm wastewater in an outdoor batch experiment for 14 days. Results showed that total nitrogen decreased from 70 mg/L to 18 mg/l in /. aquatica system and from 75 to 28 mg/L in L. flava system. Total phosphorus decreased from 8 to 0.5 mg/L in /. aquatica and from 8 to 0.8 mg/L in L. flava system. In the control system where no plant was placed, algae bloomed and total nitrogen decreased from 88 mg/L to 11 mg/L which was the best in performance. However, for total phosphorus, the control did not perform as well as those with macrophytes, where it decreased from 8.4 to 3.6 mg/L. Biomass of L. flava and I.aquatica increased 22% and 91% respectively. This indicates faster growth rate of I.aquatica. Furthermore, nitrogen uptake by I aquatica was higher than L. flava. However, both initial and final phosphorus content in L.flava were higher than I. aquatica and plant uptake of L/flava was higher than I.aquatica. This study shows that not only water quality improved, nutrients could be recycled with annual yield of L.flava and I.aquatica at 12 and 32 tons/ha respectively.